Hubungan Rotasi dengan Kinerja Perawat di RS Martha Friska Multatuli - Lahagu, Esteriani; Nurhidayah, Rika Endah; Siregar, Farida Linda Sari (Jurnal Kesehatan, 2024)
Job rotation is the displacement from one room to another, but it is still within the scope of the same job. Rotation is one of the methods for increasing quality service nursing, refreshing and preventing boredom, fulfilling the need for energy nursing in the room, and improving the skills of nurses. Job rotations at Martha Friska Multatuli Hospital have been held since 2020. This research aims to determine job rotation's correlation with nurses' performance at Martha Friska Multatuli Hospital. Research methods use descriptive correlation with cross-sectional design. The sample size in the study was as many as 71 respondents, and the technique of taking the sample was purposive sampling. The instrument used to collect data was adopted and modified from the existing rotation, and performance questionnaires were tested for validity and reliability. Data analysis using the coefficient test correlation Pearson. Research shows that nurses state that rotation at Martha Friska Multatuli Hospital is good enough for as many as 42 respondents (59.2%). It is also known that part big nurses' performance in categories good as many as 58 respondents (81.7%). Statistical results using the Pearson test obtained a ρ-value 0.004. This matter shows a correlation between positive rotation and nurses' performance at Martha Friska Multatuli Hospital. It is expected that nurses can accept the rotation decision that the hospital has determined.